Optimizing Flexor Digitorum Profundus Tendon Repair: A Narrative Review - Rishith R. Mereddy; Emily E. Zona; Camille J. LaLiberte; Aaron M. Dingle (Journal of Functional Biomaterials)
Zone II flexor digitorum profundus (FDP) tendon injuries are complex, and present significant challenges in hand surgery, due to the need to balance strength and flexibility during repair. Traditional suture techniques often lead to complications such as adhesions or tendon rupture, prompting the exploration of novel strategies to improve outcomes. This review investigates the use of flexor digitorum superficialis (FDS) tendon autografts to reinforce FDP repairs, alongside the integration of biomaterials to enhance mechanical strength without sacrificing FDS tissue. Key biomaterials, including collagen–polycaprolactone (PCL) composites, are evaluated for their biocompatibility, mechanical integrity, and controlled degradation properties. Collagen-PCL emerges as a leading candidate, offering the potential to reduce adhesions and promote tendon healing. Although nanomaterials such as nanofibers and nanoparticles show promise in preventing adhesions and supporting cellular proliferation, their application remains limited by manufacturing challenges. By combining advanced repair techniques with biomaterials like collagen-PCL, this approach aims to improve surgical outcomes and minimize complications. Future research will focus on validating these findings in biological models, assessing tendon healing through imaging, and comparing the cost-effectiveness of biomaterial-enhanced repairs with traditional methods. This review underscores the potential for biomaterial-based approaches to transform FDP tendon repair.